Mosaic Somatic Gene Recombination as a Potentially Unifying Hypothesis for Alzheimer’s Disease - Kaeser, Gwendolyn E.; Chun, Jerold (Frontiers in Genetics, 2020)
The recent identification of somatic gene recombination (SGR) in human neurons affecting the well-known Alzheimer’s disease (AD) pathogenic gene, amyloid precursor protein (APP), has implications for the normal and diseased human brain. The amyloid hypothesis has been the prevailing theory for sporadic AD (SAD) pathogenesis since the discovery of APP gene involvement in familial AD and Down syndrome. Yet, despite enormous scientific and clinical effort, no disease-modifying therapy has emerged. SGR offers a novel mechanism to explain AD pathogenesis and the failures of amyloid-related clinical trials, while maintaining consistency with most aspects of the amyloid hypothesis and additionally supporting possible roles for tau, oxidative stress, inflammation, infection, and prions. SGR retro-inserts novel “genomic complementary DNAs” (gencDNAs) into neuronal genomes and becomes dysregulated in SAD, producing numerous mosaic APP variants, including DNA mutations observed in familial AD. Notably, SGR requires gene transcription, DNA strand-breaks and reverse-transcriptase (RT) activity, all of which may be promoted by well-known AD risk factors, and provide a framework for the pursuit of new SGR-based therapeutics. In this perspective, we review evidence for APP SGR in AD pathogenesis and discuss its possible relevance to other AD-related dementias. Further, SGR’s requirement for RT activity, and the relative absence of AD in aged HIV+ patients exposed to RT inhibitors, suggest that these FDA-approved drugs may represent a near-term disease modifying therapy for AD.